PENERAPAN METODE PERSEDIAAN DALAM PERENCANAAN PAJAK - Sonu, Sri Sunarni; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2020)
Inventories are generally owned and used by companies for sale, for normal business operations, or for goods that are to be used or consumed in making goods for sale. There are two methods that can be used by taxpayers in assessing inventory and using inventory to calculate the cost of goods sold namely the first in first out method and the average method. The use of the FIFO method will result in a smaller cost of goods sold than the Average method so that the company's net income will be greater and the tax burden that must be borne by taxpayers is also greater. While the use of the Average method will result in a smaller profit margin so that for tax burden efficiency it is more effective to use the average method than the FIFO method. In other words, the smaller the profit margin obtained, the smaller the amount of tax burden that must be paid.